STRUCTURAL ANALYSIS OF BLESSING AND CURSE PHRASES IN ENGLISH AND UZBEK LANGUAGES - Norkobilova Nigora Uralovna (Bright Mind Publishing, 2026)
Blessing and curse phrases represent expressive speech acts that encode cultural values, emotional attitudes, and social norms. This article provides a contrastive structural analysis of blessing and curse phrases in English and Uzbek, focusing on their syntactic patterns, sentence types, and grammatical constructions. The study reveals both universal structural models and language-specific features shaped by cultural and pragmatic factors.
Keywords: Blessing, curse, speech acts, syntax, structure, Uzbek language, English language, paremiology, linguoculture.